Classifieds (Palíndromo, 2021)
Writing is the extended object of the title or the extended title. How does writing really differ from others? Is it not, as a verbal language, as well as others, made up of words? Here, in this document (speaking-writing), some words will be readily, without presentations, classified into five segments entitled: “mesmo fragments”, “tautological fragments”, “repeatitions fragments”, “fragments fragments”, “contextual fragments”, “fictional fragments”. There is also in the writing, we warn, the presence of absent words "     ", "     ", "     " and also non-verbal language traces coming from the bodies. In a large folding format, CLASSIFIEDS, previously, participated in the 11more11 volumes (book-cover) of the box-package “the same challenges the same”. From time to time, the writing letters of the library mesmo publish a large tabloid with collected fragments. After picking, the collected fragments, duly identified, are organized in intercrossed neighborhood areas. Readers letters are the ones who do the intercrossing, hooking a part here and correlating it with another part there and so on.
Keywords: Fragment; Repetition; Fiction; Context; Same